ANALISA PENYEBAB KEGAGALAN PIPA SUPERHEATHER BOILER - Fahrizal - (Jurnal APTEK, 2013)
This work operationts tube superheater boiler has operated by PT.Rohul Sawit Indah to determain steam and electricity power plants get failure. The failures can be make some troubles for producing at the factory. So that still need risets to the resource failure. In this cases very important to create preventif maintenance and improoving for the future. We do not hope any trouble more.In the analysis of failures need testing methode for example using Destructive and Non Destructive Testing Methods like visual, chemical composition, hardnes and metalofgrafi.From this riset should determaind same probabilities about same failure cause of quality water and envirenment to pill the boiler and modes of superheater piping, superheater is creep that operation by high temperature and high pressure with need long priode by following anealing overloads and failure.